Cell-fate transition and determination analysis of mouse male germ cells throughout development - Zhao, Jiexiang; Lu, Ping; Wan, Cong; Huang, Yaping; Cui, Manman; Yang, Xinyan; Hu, Yuqiong; Zheng, Yi; Dong, Ji; Wang, Mei; Zhang, Shu; Liu, Zhaoting; et al. (Nature communications, 2021)
Mammalian male germ cell development is a stepwise cell-fate transition process; however, the full-term developmental profile of male germ cells remains undefined. Here, by interrogating the high-precision transcriptome atlas of 11,598 cells covering 28 critical time-points, we demonstrate that cell-fate transition from mitotic to post-mitotic primordial germ cells is accompanied by transcriptome-scale reconfiguration and a transitional cell state. Notch signaling pathway is essential for initiating mitotic arrest and the maintenance of male germ cells’ identities. Ablation of HELQ induces developmental arrest and abnormal transcriptome reprogramming of male germ cells, indicating the importance of cell cycle regulation for proper cell-fate transition. Finally, systematic human-mouse comparison reveals potential regulators whose deficiency contributed to human male infertility via mitotic arrest regulation. Collectively, our study provides an accurate and comprehensive transcriptome atlas of the male germline cycle and allows for an in-depth understanding of the cell-fate transition and determination underlying male germ cell development. The full-term developmental profile of male germ cells remains undefined. Here, the authors use single-cell sequencing to investigate the transcriptome landscapes of mouse male germ cells throughout development and find several critical regulators for prenatal cell-fate determination.